Effect of Gd2O3 on the radiation shielding, physical, optical and luminescence behaviors of Gd2O3–La2O3–ZnO–B2O3–Dy2O3 glasses. (August 2021) - Kaewjaeng, S.; Wantana, N.; Kothan, S.; Rajaramakrishna, R.; Kim, H.J.; Limsuwan, P.; Kaewkhao, J.
Abstract: The present work focuses on lead-free glasses, their shielding behavior, and other optical studies. The glass composition with xGd2 O3 +10La2 O3 +10ZnO+(79-x) B2 O3 +1Dy2 O3, x = 0, 5, 10, 15, 20 mol% were prepared to the characterization on physical, absorption spectra, photo-, radioluminescence, and radiation shielding properties. In the experimental results, the density of Gd-1Dy glass samples increases with the increase of Gd 3+ ions concentrations. The ten-strong peak in the 5Gd-1Dy glass of absorption spectra in UV–Vis–NIR regions. The white photoluminescence spectra base of Gd-1Dy glass samples can be generated under excitation at 351 nm makes the strongest emission of Dy 3+ ions and excitation through energy transfer from Gd 3+ in Gd-1Dy glass samples with 275 and 351 nm. This strong white emission of Dy 3+ ions also strong in x-ray luminescence and performs the integral scintillation efficiency of 33% when compared with BGO crystal. The radiation shielding properties in the diagnostic medicine energies region are correlated, the values of glass samples better than commercial windows, bricks, and concrete. The HVL values of glass sample at 15 and 20 mol% of Gd2 O3 has been found better than X-ray windows. The corollaries of Gd-1Dy glass samples can be a candidate for radiation detector and lead-free radiation shielding materials in future. Highlights: Effect of Gd2 O3 on BaO: ZnO: B2 O3 : Dy2 O3 was studied. Density of Gd-1Dy glass increases with the increase of Gd 3+ . White photoluminescence spectra and ET process was observed. Scintillation efficiency as 33% when compared with BGO crystal. HVL values of glass at 15 and 20 mol% of Gd2 O3 better than X-ray windows.